Citizens of Liepāja city Teodors and Nikolajs Bredžs-Briedis in business and engineering sciences - Gaitniece, Lāsma (History of Engineering Sciences and Institutions of Higher Education, 2018)
The article is dedicated to the citizens of Liepāja city Teodors Bredžs- Briedis (1885–1940) and Nikolajs Bredžs-Briedis (1909–1989) – father and son. Father Teodors Bredžs-Briedis was an entrepreneur in Liepāja city, but his son, Nikolajs, graduate of the Faculty of Chemistry (1936) of the University of Latvia, emigrated to the United States of America at the end of the Second World War. Nikolajs Bredžs-Briedis had a brilliant scientist’s career – his research work in the metal welding industry was valued in 1955 by the Lincoln Gold Medal Award of the American Welding Society. In 1956, he was admitted to the US Honorary Society of Scientists and Researchers. Nikolajs Bredžs-Briedis has received 27 patents and is the author of 14 scientific publications.